Thermal effect on mechanical characteristics of drinking water sludge brick incorporated with rice husk ash - Zulfahmi Ali Rahman,; Nor Maisalhah Mohd Saleh,; Wan Mohd Razi Idris,; Tukimat Lihan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Brick is among the important construction materials and commonly manufactured from mixtures of clay or sand, lime and cement. Due to limited natural resources for raw materials and highly demand for brick in construction industry have gradually increased the market price of each unit. Therefore, alternative sources are required such utilization of drinking water sludge (DWS) and rice husk ash (RHA) are potentially used as base and/or incorporated materials for manufacturing alternative brick. In this study, the brick samples which had been developed from mixtures of DWS and RHA (D80 brick) were subjected to different firing temperatures of 300oC and 500oC. The results of this study were compared to that of unfired brick and bricks which developed from 100% DWS content (D100 brick). The result also shows the volume shrinkage significantly increased at firing temperature of 500oC and was more apparently affected the D100 brick if compared to that of D80 brick. As firing temperatures were increased, the density of both brick samples decreased with D100 brick more prominent than D80 brick. The effect of temperature on the water absorption and compressive strength clearly increased especially for the D80 bricks, respectively. The effect of temperature is closely related to the presence of rice husk ash as this organic matter destroyed at high firing temperature of 500oC. The results obtained in this study suggested that firing temperature can modify and enhance the studied mechanical characteristics.